Associations Between Lumbar Vertebral Bone Marrow and Paraspinal Muscle Fat Compositions—An Investigation by Chemical Shift Encoding-Based Water-Fat MRI - Sollmann, Nico; Dieckmeyer, Michael; Schlaeger, Sarah; Rohrmeier, Alexander; Syvaeri, Jan; Diefenbach, Maximilian N.; Weidlich, Dominik; Ruschke, Stefan; Klupp, Elisabeth; Franz, Daniela; Rummeny, Ernst J.; Zimmer, Claus; et al. (Frontiers in Endocrinology, 2018)
Purpose: Advanced magnetic resonance imaging (MRI) methods enable non-invasive quantification of body fat situated in different compartments. At the level of the lumbar spine, the paraspinal musculature is the compartment spatially and functionally closely related to the vertebral column, and both vertebral bone marrow fat (BMF) and paraspinal musculature fat contents have independently shown to be altered in various metabolic and degenerative diseases. However, despite their close relationships, potential correlations between fat compositions of these compartments remain largely unclear. Materials and Methods: Thirty-nine female subjects (38.5% premenopausal women, 29.9 ± 7.1 years; 61.5% postmenopausal women, 63.2 ± 6.3 years) underwent MRI at 3T of the lumbar spine using axially- and sagittally-prescribed gradient echo sequences for chemical shift encoding-based water-fat separation. The erector spinae muscles and vertebral bodies of L1–L5 were segmented to determine the proton density fat fraction (PDFF) of the paraspinal and vertebral bone marrow compartment. Correlations were calculated between the PDFF of the paraspinal muscle and bone marrow compartments. Results: The average PDFF of the paraspinal muscle and bone marrow compartments were significantly lower in premenopausal women when compared to postmenopausal women (11.6 ± 2.9% vs. 24.6 ± 7.1% & 28.8 ± 8.3% vs. 47.2 ± 8.5%; p<0.001 for both comparisons). In premenopausal women, no significant correlation was found between the PDFF of the erector spinae muscles and the PDFF of the bone marrow of lumbar vertebral bodies (p=0.907). In contrast, a significant correlation was shown in postmenopausal women (r=0.457, p=0.025). Significance was preserved after inclusion of age and body mass index (BMI) as control variables (r=0.472, p=0.027). Conclusion: This study revealed significant correlations between the PDFF of paraspinal and vertebral bone marrow compartments in postmenopausal women. The PDFF of the paraspinal and vertebral bone marrow compartments and their correlations might potentially serve as biomarkers; however, future studies including more subjects are required to evaluate distinct clinical value and reliability. Future studies should also follow-up our findings in patients suffering from metabolic and degenerative diseases to clarify how these correlations change in the course of such diseases.